Neutral models predict biogeographical patterns of soil microbes at a local scale in Mediterranean heathlands, South Africa. Issue 2 (4th May 2019) - Moroenyane, I.; Chimphango, S.B.M.; Dong, K.; Tripathi, B.; Singh, D.; Adams, J.M.
Abstract : The South African Fynbos is the smallest floristic kingdom with high levels of endemism and where fire dominates the landscape. However, drivers of soil microbial distribution and diversity are still poorly understood. This study aims to highlight the biogeographical patterns of bacterial and fungal communities and elucidate the mechanisms that mediate their distribution. Soil samples were collected from four Fynbos vegetation types and microbial dynamics were examined using Illumina sequencing of the 16S rRNA bacterial gene and fungal ITS region. Bacterial alpha diversity significantly varied across all Fynbos vegetation types, whilst only the fungal community structure was significantly influenced by vegetation types and environmental variables. The relative abundance of major phyla was similar across all Fynbos types with the exception of Gemmatimonadetes, Cyanobacteria, Ascomycota and Zygomycota . Lastly, neutral models were the best predictor of the abundance and distribution of operational taxonomic units (OTUs) across all Fynbos vegetation types, suggesting that during the winter months dispersal limitations play a role in microbial community assembly. Overall, taken together with previous studies from the region, this study provides novel insight into the processes that modulate the biogeographical patterns of soil microbes and contributes to our knowledge of factors that mediate microbial ecology in diverse ecosystems.